1969
DOI: 10.1139/v69-621
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the decomposition of tetra-alkylammonium salts in solution. Part II. Dependence of the activation parameters on the structure of the substrate

Abstract: The enthalpy and entropy of activation for the decomposition reaction of seven tetra-alkylammonium iodides in chloroform solution have been measured. All the salts contained the benzyl group attached to the nitrogen atom and decomposed to yield benzyl iodide and a tertiary amine as the only products.A Hammett free energy correlation is made and used to deduce the nature of the transition state, and a rationalization of the variation of the enthalpy and entropy of activation with the structure of the substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1970
1970
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…5) was +2.04. The sign of the p value indicates that the positive charge on the quaternary ammonium nitrogen has decreased in the transition state of this reaction (18). An estimate of the extent to which the positive charge has been reduced and thus the amount of carbon-nitrogen bond rupture that has occurred in the transition state, can be obtained by comparing the observed p value with those found in similar reactions of other quaternary ammonium salts.…”
Section: Hammett P Valuementioning
confidence: 79%
See 1 more Smart Citation
“…5) was +2.04. The sign of the p value indicates that the positive charge on the quaternary ammonium nitrogen has decreased in the transition state of this reaction (18). An estimate of the extent to which the positive charge has been reduced and thus the amount of carbon-nitrogen bond rupture that has occurred in the transition state, can be obtained by comparing the observed p value with those found in similar reactions of other quaternary ammonium salts.…”
Section: Hammett P Valuementioning
confidence: 79%
“…The p-methoxy-N,N-dimethylaniline was prepared from p-anisidine using the method described by Leffek (18). The p-chloro-N,N-dimethylaniline was prepared from p-chloroaniline using the method described by Chambers (27).…”
Section: Methodsmentioning
confidence: 99%
“…These isotope effects are considerably larger than those observed for SN2 reactions and Leffek and KO very reasonably concluded that these reactions must involve the formation of a carbonium ion intermediate in the slow step of the reaction. Based on this and other evidence (8,9) these authors proposed that the reacZThe magnitudes of secondary a-deuterium kinetic isotope effects for SN2 reactions will also be affected by a change in the nucleophile.…”
Section: Table 1 Maximum Secondary A-deuterium Kineticmentioning
confidence: 93%
“…Leffek and co-workers have extensively studied the decomposition of aralkyldimethylphenylammonium halides to aralkyl halides and dimethylaniline (the reverse of the Menschutkin reaction) in chloroform (1)(2)(3)(4)(5), eq. [I].…”
Section: Introductionmentioning
confidence: 99%